2003
DOI: 10.1065/espr2001.12.103
|View full text |Cite
|
Sign up to set email alerts
|

Acetochlor as a soil pollutant

Abstract: Acetochlor is a widely used herbicide all over the world. Similarly to other organic pollutants, the environmental fate of the acetochlor is strongly related to its adsorption properties. Static adsorption equilibrium measurements were carried out at 25 degrees C on different types of Hungarian soils characterized by varying amounts of organic matter and pH values. Isotherms obtained under different conditions, as well as on various soils, exhibit a similar shape, thus indicating a two-step adsorption process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Although acetochlor is one of the most frequently used herbicides in Slovakia, there is no data referring to its sorption behavior in natural solids. Even throughout the world, only a little data is available for acetochlor sorption (Kholodov et al 2005;Lengyel and Földényi 2003;Liu et al 2000;Wang et al 1999;Zheng and Ye 2002) and very little for its desorption (Taylor et al 2004). Previous studies based on soil column and sorption experiments have shown that acetochlor presents a risk of groundwater contamination (Balinova 1997;Zheng and Ye 2002), consistent with its frequent presence observed in groundwater (Barbash et al 2001;Kolpin et al 1996Kolpin et al , 1998.…”
mentioning
confidence: 68%
“…Although acetochlor is one of the most frequently used herbicides in Slovakia, there is no data referring to its sorption behavior in natural solids. Even throughout the world, only a little data is available for acetochlor sorption (Kholodov et al 2005;Lengyel and Földényi 2003;Liu et al 2000;Wang et al 1999;Zheng and Ye 2002) and very little for its desorption (Taylor et al 2004). Previous studies based on soil column and sorption experiments have shown that acetochlor presents a risk of groundwater contamination (Balinova 1997;Zheng and Ye 2002), consistent with its frequent presence observed in groundwater (Barbash et al 2001;Kolpin et al 1996Kolpin et al , 1998.…”
mentioning
confidence: 68%
“…In the river water, acetochlor was difficult to hydrolysis and the half‐life is more than 1386 days (Zheng and Ye ). Due to its low adsorptive potential in soils, heavily applied acetochlor was rather mobile, posing a potential risk to the aquatic (Lengyel and Földényi ). Studies have proved the presence of acetochlor in groundwater as well as in surface water (Kolpin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Acetochlor (2-chloro-N-(ethoxymethyl)-N-(2-ethyl-6-methylphenyl)-acetamide) is a common herbicide all over the world (Lengyel and Foldenyi, 2003), which has been widely used in China (Ye, 2003). Previous studies have demonstrated the presence of acetochlor in surface water (Hladik et al, 2008), soil (Chao et al, 2007), and sediment (Xue et al, 2005).…”
Section: Introductionmentioning
confidence: 99%